2023
DOI: 10.7759/cureus.41252
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal Syndrome: A Literature Review

Abimbola O Ajibowo,
Okelue E Okobi,
Erhieyovbe Emore
et al.

Abstract: Cardiorenal syndrome (CRS) is a condition characterized by the intricate two-way relationship between the heart and kidneys, which can lead to acute or chronic dysfunction in these organs. The interplay between cardiorenal connectors and both hemodynamic and non-hemodynamic factors is crucial to understanding this syndrome. The clinical importance of these interactions is evident in the changes observed in hemodynamic factors, neurohormonal markers, and inflammatory processes. Identifying and understanding bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…Accordingly, we found that renal sham surgery of 45 min did not cause any significant deterioration in the cardiac physiological function (measured via LVDP, LVEDP, and RPP) or inflict any significant tissue injury (measured via histopathology, TUNEL, and cardiac injury markers). In general, cardio renal mediators that initiate the cross-talk between the heart and kidney can cause organ dysfunction [ 46 ]. One of these mediators is metabolites’ altered products that may intensify with stress factors like surgery [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we found that renal sham surgery of 45 min did not cause any significant deterioration in the cardiac physiological function (measured via LVDP, LVEDP, and RPP) or inflict any significant tissue injury (measured via histopathology, TUNEL, and cardiac injury markers). In general, cardio renal mediators that initiate the cross-talk between the heart and kidney can cause organ dysfunction [ 46 ]. One of these mediators is metabolites’ altered products that may intensify with stress factors like surgery [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survey design also made it challenging to assess other potentially relevant factors, such as the severity of mental disorders [ 28 ], specific types of mental disorders, and the use of psychotropic medications [ 29 ], which may confound the study outcomes. Furthermore, the data was limited to individuals residing in households and able to respond to survey questions, which limits the generalizability of the findings to individuals experiencing homelessness, who are at higher risk of mental disorders and have limited access to mental healthcare services [ 30 - 34 ]. Prospective studies should consider longitudinal datasets, employ objective measures, examine the experiences of individuals with mental conditions in psychiatric treatment settings, and explore the impact of knowledge on psychosocial factors affecting CRC screening participation, particularly within specific populations.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a predominant renal problem often treated by surgical and non-surgical methods where the outcome of surgical procedures negatively influences the other organs including the brain, lung, heart and liver [ 2 , 3 ]. Many studies have reported the complex interaction between the heart and kidney in various pathological conditions, which often leads to cardiorenal syndrome (CRS), which can manifest in dual organ dysfunction [ [4] , [5] , [6] ] [ [4] , [5] , [6] ] [ [4] , [5] , [6] ]. Incidentally, cardiac events such as heart attacks, heart failure and heart rhythm disorders were reported in association with different renal surgery [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by transient obstruction of blood flow to the kidneys, with inadequate local blood supply [ 8 , 10 ]. Even though the focus of such surgical interventions is primarily aimed to restore renal function, recent evidence suggests that these procedures may have broader implications on distant organs, particularly the heart (CRS type 3) [ 4 , 6 ]. However, the limited information available in this direction indicates that cardiac patients who experienced AKI are two times more likely to get admitted to the hospital for heart failure within 1.4 years.…”
Section: Introductionmentioning
confidence: 99%